Recurrent Hemoptysis and a Mass in the Thorax in an Infant: The Split Notochord Syndrome - Mutlu Uysal Yazici; Saniye Ekinci; Ozlem Keskin Turkmen; Ebru Gunes Yalcin; Arbay O. Ciftci; Safak Gucer; Diclehan Orhan; Ilhan Tezcan (Georg Thieme Verlag KG, 2014)
Abstract Split notochord syndrome is a rare group of developmental abnormalities caused by abnormal splitting or deviation of the notochord clinically resulting in the duplicated bowel associated with vertebral anomalies. We report on a case of 11-month-old female infant with mediastinal hyperechogenic cyst and intestinal duplication cyst associated with T5-T6 hemivertebrae, scoliosis, and nonfusion of posterior part of T6 vertebrae, presenting with severe hemoptysis and hematemesis. The cysts were surgically removed, and histopathologic analysis revealed that the mediastinal cyst was lined by gastric mucosa and intestinal one was lined with gastric mucosa including ectopic pancreatic tissue. After removal of the lesion the patient made an uneventful recovery and shows no signs of long-term pulmonary sequelae.